Detection of the antibacterial efficacy of Paenibacillus polymyxa against Xanthomonas oryzae pv. oryzae in rice seedlings, and the antimicrobial related genes - Yasmine Abdallah; Ranya M. El-Ashmony; Abdelrazek S. Abdelrhim (Novel Research in Microbiology Journal, 2020)
Paenibacillus polymyxa bacterium has been known as a biocontrol agent (BCA) for various plant diseases, and it promotes the growth of several treated plants. On the other hand, Xanthomonas oryzae pv. oryzae (Xoo) is an important bacterial pathogen that causes bacterial leaf blight (BLB) to rice plants, and cause high yield loss during the growing season. In this study, P. polymyxa SX3 inhibited the in vitro growth of Xoo by 80% and affected the biofilm formation. Also, the cell membrane of Xoo lost its permeability after treating it with culture filtrate of P. polymyxa at its MIC (40%). Transmission electron microscopic (TEM) observations showed an influence of the culture filtrate of P. polymyxa on the cell morphology of Xoo. Applying P. polymyxa decreased the severity of bacterial leaf blight on rice seedlings to 4.9%, compared to 42.5% of the control. Moreover, this strain also improved the growth parameters of the rice seedlings significantly by increasing the shoot length, root length, fresh and dry weight by 166.7%, 168.2%, 100%, and 255.6%; respectively, compared to the positive control (Xoo only). Three antimicrobial related genes; pmxB, pmxD, and Fusdel were detected in P. polymyxa SX3 using nine specific gene markers. The aims of the study were to investigate the impact of P. polymyxa SX3 on in vitro growth of Xoo, in vivo growth of the rice seedlings in the greenhouse, and to detect the presence of related antimicrobial genes.